The Effects of Asynchronous Computer Voice Conferencing on L2 Learners’ Speaking Anxiety - Poza, María Isabel Charle (IALLT Journal of Language Learning Technologies, 2011)
This study investigated the influence of a computer voice conferencing environment (Wimba) on learners’ anxiety when speaking in a foreign language. Several instruments were used for data collection: A demographic survey, the Computer Anxiety Index (CAIN), the Foreign Language Classroom Anxiety Scale (FLCAS), the Wimba Anxiety Scale, student interviews, and a rubric developed for the evaluation of risk-taking. Results indicate that there is a strong potential for the reduction of anxiety associated with the Wimba environment. This was due to the elimination of the time pressure of the classroom and opportunity to edit student contributions. Increased risk-taking, in terms of the quantity and quality of the output produced by students, and reduced fear of negative evaluation were also found in the electronic environment. The conditions of the facility where the Wimba environment is accessed, i.e. a language laboratory, were found to hinder Wimba’s anxiety-reducing potential.